The Utilization of Waste Cooking Oil As a Material of Soap - Mustakim Mustakim; Rahmad Taufik; Trismawati Trismawati (Journal of Development Research, 2020)
Cooking oil is a vegetable oil as a glyceride compound from various fatty acids. Cooking oil can be used up to 3-4 times for cooking. If cooking oil is used repeatedly, the fatty acids will be more saturated and can change color. The waste cooking oil is said to have been damaged and is not good for consumption and can pollute the environment. Appropriate technology is a technology designed for a particular society to be adapted to environmental, political, cultural, social, and economics aspects. The purpose of appropriate technology is to be able to save money, be easy to maintain, and minimize costs to the community. The appropriate technology in this study aims to facilitate the production process of making soap or can also achieve the desired goals effectively in a place or production. The results of this research are mixer and soap products, which are mixers made from used materials to be used as soap making tools. For the processing of soap products, cooking oil waste is used, which is known that the cost of production per soap bar is Rp578.00. Researchers sell it at a price of Rp1,000.00. The Break Event Point (BEP) value is 200 bars of soap per year or Rp200,000.00. Net Present Value (NPV) in 4 years is Rp9,498,061.00, and the Return of Investment (ROI) from the payback period is 0.9 months.